Photochemical Internalization Enhanced Vaccination Is Safe, and Gives Promising Cellular Immune Responses to an HPV Peptide-Based Vaccine in a Phase I Clinical Study in Healthy Volunteers - Otterhaug, Tone; Janetzki, Sylvia; Welters, Marij J. P.; Håkerud, Monika; Nedberg, Anne Grete; Edwards, Victoria Tudor; Boekestijn, Sanne; Loof, Nikki M.; Selbo, Pål Kristian; Olivecrona, Hans; van der Burg, Sjoerd H.; Høgset, Anders (Frontiers in Immunology, 2021)
Background and aims Photochemical internalization (PCI) is a technology for inducing release of endocytosed antigens into the cell cytosol via a light-induced process. Preclinical experiments have shown that PCI improves MHC class I antigen presentation, resulting in strongly enhanced CD8+ T-cell responses to polypeptide antigens. In PCI vaccination a mixture of the photosensitizing compound fimaporfin, vaccine antigens and an adjuvant is administered intradermally followed by illumination of the vaccination site. This work describes an open label, phase I study in healthy volunteers, to assess the safety, tolerability and immune response to PCI vaccination in combination with the adjuvant poly-ICLC (Hiltonol) (ClinicalTrials.gov Identifier: NCT02947854). Methods The primary objective of the study was to assess the safety and local tolerance of PCI mediated vaccination, and to identify a safe fimaporfin dose for later clinical studies. A secondary objective was to analyze the immunological responses to the vaccination. Each subject received 3 doses of HPV16 E7 peptide antigens and two doses of Keyhole Limpet Hemocyanin (KLH) protein. A control group received Hiltonol and vaccine antigens only, whereas the PCI groups in addition received fimaporfin + light. Local and systemic adverse effects were assessed by standard criteria, and cellular and humoral immune responses were analyzed by ELISpot, flow cytometry and ELISA assays. Results 96 healthy volunteers were vaccinated with fimaporfin doses of 0.75 to 50 µg. Doses below 17.5 µg were safe and tolerable, higher doses exhibited local tolerability issues in some study subjects, mainly erythema and pain during illumination. There were few, and only mild and expected systemic adverse events. The employment of PCI increased the number of subjects exhibiting a T-cell response to the HPV peptide vaccine about 10-fold over what was achieved with the antigen/Hiltonol combination without PCI. Moreover, the use of PCI seemed to result in a more consistent and multifunctional CD8+ T-cell response. An enhancement of the humoral immune response to KLH vaccination was also observed. Conclusions Using PCI in combination with Hiltonol for intradermal vaccination is safe at fimaporfin doses below 17.5 µg, and gives encouraging immune responses to peptide and protein based vaccination.